The Influence of Financial Literacy Towards Financial Behavior and its Implication on Financial Decisions: A survey of President University Students in Cikarang - Bekasi - Suresh Kumar; Christalita Watung; Josephine Eunike; Lusianna Liunata (FIRM Journal of Management Studies, 2017)
ABSTRACT                                                                                                                                 Financial literacy consists of financial knowledge, financial attitudes, and financial behavior. To be financially literate is important in order to make a good financial decision. Young adult especially college students are facing tough financial decision in today’s demanding financial environment which will affect their financial behavior. This research objective is to find out the influence of financial literacy on financial behavior and how financial behavior influences on financial decision among college students. The research applied quantitative method with 337 samples as respondents taken from President University students. This research applied convenience sampling technique. The results of this research show that there’s a significant relation between financial literacy to financial behavior and from financial behavior to financial decision. Since parents are the first people for the children, they should give good understanding about financial matter towards their children that may affect to children’s financial behavior and the decision that will be made later in the future. Education institution may consider about students’ ages and economy status in making financial education program. Hence, it will be more effective to increase financial literacy among college students. Due to its limitation, it is recommended for future researchers to add more variables such as race, religion, and culture to have deeper understanding about financial behavior in its implication on financial decision of college students.Keywords: financial literacy, financial behavior, financial decision